2020
DOI: 10.1002/jgc4.1230
|View full text |Cite
|
Sign up to set email alerts
|

Racial and ethnic differences in genetic counseling experiences and outcomes in the United States: A systematic review

Abstract: As genetic counseling services expand and reach a wider catchment of the population, there is a critical need to better understand the impact of services on a greater diversity of patients. We conducted a systematic review to evaluate genetic counseling experiences and outcomes among racial and ethnic minorities. Six databases extracted articles published from 2005 to 2019 that assessed genetic counseling participation, knowledge and awareness, motivators, barriers, perceptions, and outcomes for racial and eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 66 publications
1
21
0
Order By: Relevance
“…This was true after controlling for educational attainment and income, suggesting there are additional barriers to awareness of the GC profession beyond just educational differences as has been reported previously (Ladson-Billings, 2006). Non-White individuals may not have the opportunities that White individuals do to learn about or be referred to GC as often as do White patients (Ladson-Billings, 2006;Southwick et al, 2020). This is demonstrated by two recent studies; one study reported that Black patients with young-onset colorectal cancer were less likely to be referred to and attend genetic counseling sessions compared with White patients (Dharwadkar et al, 2020) and the second study found that Non-Hispanic White patients were more likely to be referred for cancer genetic services based on family history when compared to Non-Hispanic Black, Hispanic, and Asian patients (Chaoman-Davis et al,…”
Section: Discussionmentioning
confidence: 74%
“…This was true after controlling for educational attainment and income, suggesting there are additional barriers to awareness of the GC profession beyond just educational differences as has been reported previously (Ladson-Billings, 2006). Non-White individuals may not have the opportunities that White individuals do to learn about or be referred to GC as often as do White patients (Ladson-Billings, 2006;Southwick et al, 2020). This is demonstrated by two recent studies; one study reported that Black patients with young-onset colorectal cancer were less likely to be referred to and attend genetic counseling sessions compared with White patients (Dharwadkar et al, 2020) and the second study found that Non-Hispanic White patients were more likely to be referred for cancer genetic services based on family history when compared to Non-Hispanic Black, Hispanic, and Asian patients (Chaoman-Davis et al,…”
Section: Discussionmentioning
confidence: 74%
“…Other studies have explored the use of narrative educational tools for at-risk Latinas to improve psychosocial outcomes [19,20]. The vast majority of literature on genetic counseling interventions in diverse populations has focused mainly on cancer genetics [21], and there is a dearth of literature on barriers to communication in racially and ethnically diverse pediatric patient populations and their families. Digital applications that display personalized genetic testing results in a way that addresses lowhealth literacy, includes images, and provides information in both English and Spanish can be leveraged to improve understanding.…”
Section: Introductionmentioning
confidence: 99%
“…All participants are followed by a physician in the participating institutions. Patient participants are 0-21 years of age; young adults (18-21) who are cognitively intact are included in this study provided that their parent(s) or legal guardian(s) also agree to participate. All participants have a currently undiagnosed, suspected genetic cause of their specific neurologic, immunologic, or cardiac disorders.…”
Section: Study Populationmentioning
confidence: 99%
“…Other studies have explored the use of narrative educational tools for atrisk Latinas to improve psychosocial outcomes (19,20). The vast majority of literature on genetic counseling interventions in diverse populations has focused mainly on cancer genetics (21), and there is a dearth of literature on barriers to communication in racially and ethnically diverse pediatric patient populations and their families. Digital applications that display personalized genetic testing results in a way that addresses low-health literacy, includes images, and provides information in both English and Spanish can be leveraged to improve understanding.…”
Section: Introductionmentioning
confidence: 99%